A Study on Influence of Inlet Pressure and Fiber Architecture on the Quality of Sample Made From VARTM (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In recent years, research is underway worldwide by scientists to successfully replacethe majority of structural components that are denser, high weight and are costly with fiberreinforced polymer (FRP) composites materials that are lightweight and low cost withoutsacrificing strength requirements in various applications. Among the available compositefabrications techniques, Resin infusion process is a competent and most effective techniquewhich has been successfully used by the industries for production of complex FRP compositecomponents and structures with intricate geometric details. However in any fabrication process,understanding the effect of critical process parameters is highly important to ensure high qualityof final composite materials with superior mechanical properties. Therefore, the present study isfocused on studying the effect of critical process parameters such as fiber architectures, numberof layers and inlet vacuum in the mould on the quality and mechanical properties of the eglass/polyester composite laminates fabricated by means of resin infusion technique. Threedifferent fiber architectures: (i) Chop strand (ii) Woven mat and (ii) unidirectional mat areselected. Moreover, three different fiber reinforcements layers (as 4 layers, 5 layers and 6 layers)with varied vacuum pressures: (i) 200 mm of Hg, (ii) 300 mm of Hg, and (iii) 400 mm of Hg areselected in the present study for preparation of samples. The results indicated a considerableeffect of inlet pressure and the fiber architecture on the materials performance.